Penggunaan Kata κοινωνία Dalam 1 Korintus 1:9 Dan Interpretasinya Dalam Mengatasi Perpecahan Di Jemaat - Warseto Freddy Sihombing; Seri Antonius (KAMASEAN: Jurnal Teologi Kristen, 2022)
The purpose of this research is to explore the meaning of the word (koinonia: fellowship) which is found in 1 Corinthians 1:9. In Paul's letter, it is explained about the call as believers to share in fellowship with Jesus Christ. God calls believers to fellowship with Jesus Christ, the Son of God, which is God's ultimate goal. This fellowship of believers parallels the fellowship of the Father, Jesus Christ, and the Holy Spirit. This fellowship is a supernatural (spiritual) interaction between the person of God and His church on earth which is the theological implication of the concept of the Triune God. Using the hermeneutic method, the writer finds that Paul's explanation regarding (koinonia: fellowship) is the main basis for providing solutions to the problem of division that occurred in the Corinthian church. This is also an example for the congregation today in finding the best solution for the problem of division that occurs. Abstrak: Tujuan penelitian ini adalah untuk menggali makna kata κοινωνία (koinonia: persekutuan) yang terdapat dalam 1 Korintus 1:9. Dalam surat Paulus ini dijelaskan mengenai panggilan sebagai orang percaya untuk turut mengalami persekutuan dengan Yesus Kristus. Allah memanggil orang percaya kepada persekutuan dengan Yesus Kristus, Anak Allah, yang merupakan tujuan utama Allah. Persekutuan orang percaya ini pararel dengan persekutuan antara Bapa, Yesus Kristus, dan Roh Kudus. Persekutuan ini adalah sebuah interaksi supranatural (rohani) antara pribadi Allah dan gereja-Nya di bumi yang merupakan implikasi teologis dari κοινωνία terhadap konsep Allah Trituggal. Dengan metode hermeneutik penulis menemukan bahwa penjelasan Paulus berkaitan dengan κοινωνία (koinonia: persekutuan) ini menjadi dasar utama untuk memberikan solusi dalam masalah perpecahan yang terjadi di jemaat Korintus. Hal ini juga menjadi contoh bagi jemaat saat ini dalam menemukan solusi terbaik untuk persoalan perpecahan yang terjadi.